Elements of Youth and Adult Education in Brazil and Cuba - Gaya, Sidneya Magaly; Rampinelli, Waldir (Pontifícia Universidade Católica de São Paulo, 2021)
This article proposes researching and understanding Cuban educational policies as significantly capable and hence as potentially contributing to Brazilian public policy, especially with regard to youth and adult education. For this purpose, Cuba is considered, like Brazil, as a country with a colonial history, a dependent form of capitalism, a Catholic tradition, a location in the Americas, and, especially, a system of universal elementary education, which was achieved despite the economic embargo in place since 1959.